Preliminary study of KNN thin films doped by rare-earths for sensor applications - Mohd Hatta, Maziati Akmal; Al-Amani, Umar; Abdul Rashid, Mohd Warkih; Azmi, Nurul Azuwa (2015)
Among ferroelectrics systems, potassium sodium niobate KNN) has drawn much attention due to a clear-cut advantage of high piezoelectric and ferroelectric performances. The volatility of alkaline element (K,Na) is detrimental to the stoichiometry of KNN, contributing to the formation of intrinsic defects. Thus, the primary goal of this study is to design a solution to overcome the volatility issue of KNN. Introduction of rare-earth cations in the host KNN could reduce the vacancies in KNN. Currently, three arrays of dopants were integrated into KNN. In this preliminary work, a sol-gel technique was employed to produce a thin film that can be utilized later in the sensor applications. The structural and electrical properties were characterized using Raman spectroscopy and 2-point probe equipment, respectively. The typical Raman spectra of KNN thin films were shifted towards lower or higher wavenumbers depending on the cations deficiencies or redundancies. The conductivity of thin films was found to be increased as the dopant concentration was increased.